Folk-Studing Tendencies of Ivan Franko in the Development of the Music Ethnopedagogics - Myron Vovk (Pedagogical Discourse, 2012)
On the bases of study, analyses and systematization of archival materials, folk tendences of development of music ethnopedagogics in Ivan Franco’s creation are revealed.